ANALISIS RASIO CAMEL PADA PT. BANK PEMBIAYAAN RAKYAT SYARIAH RAHMAH HIJRAH AGUNG KOTA LHOKSEUMAWE DAN PT. BANK PERKREDITAN RAKYAT SABEE MEUSAMPE KABUPATEN ACEH UTARA TAHUN 2015-2016 - Silvia Ulfa; M. Lutfi Al Fahmi (LPPM STIE Lhokseumawe, 2017)
The purpose of this study is to determine the soundness of banks in PT. Bank Pembiayaan Rakyat Syariah (BPRS) Rahmah Hijrah Agung Kota Lhokseumawe and PT. Bank Perkreditan Rakyat (BPR) Sabee meusampe using CAMEL ratio from 2015 to 2016, and to know how predicate bank performance in PT. Bank Pembiayaan Rakyat Syariah (BPRS) Rahmah Hijrah Agung Kota Lhokseumawe and PT. Bank Perkreditan Rakyat (BPR) Sabee Meusampe Kabupaten Aceh Utara Court from 2015 until 2016. the authors are interested in conducting research with the title “Ratio Analysis CAMEL In the Bank Pembiayaan Rakyat Syariah (BPRS) Rahmah Hijrah Agung Kota Lhokseumawe and PT. Bank Perkreditan Rakyat (BPR) Sabee Meusampe Kabupaten Aceh Utara “. In this research method used is quantitative method such as the numbers of the Balance Sheet, Profit / Loss Report, Report of Assets Quality, and Capital Adequacy Reports. Qualitative research with descriptive approach to measure the financial performance of banks to perform calculations using financial ratios CAMEL (Capital, Assets, Managemet Earnings, and Liquidity). The results of the assessment results of BPRS Rahmah Hijrah Agung and PT. Bank Perkreditan Rakyat (BPR) Sabee Meusampe Kabupaten Aceh Utara Great move by using the CAMEL from 2015 to 2016 received the title FAIR . Suggestions in this research is to improve the quality of productive assets is a good idea if the BPRS RHA and BPR Sabee Meusampe maintain or increase the number of PPAP formed so as to cover risks that may arise if the velocity of earning assets less current and in line with efforts to reduce the number of troubled loans, particularly those categorized bad credit.